Formação de agregados gelatinosos em culturas de microalgas de um reservatório eutrofizado (rio Tietê/SP) - Ortolano, Pedro Ivo Coelho (2005)
This work presents original data about aggregate formation by two diatoms, Aulacoseira granulata and Thalassiosira cf. duostra, isolated from Barra Bonita reservoir (Tietê river/ SP). Experiments were performed using a Couette floculator, a machine that promotes laminar fluid shear rates (G, s-1), in which particles in movement with several velocities will shock. Depending on their stickiness, the particles may or may not form aggregates. It was determined that different fluid shear rates can affect distinctly aggregate formation by the two algal species. At shear rates of 10 s-1, T. cf. duostra formed aggregates more intensively than A. granulata. However, aggregate formation by A. granulata was greater at a lower shear rate (3 s-1). The role of exopolysaccharides (EPS) produced by these species in aggregate formation by their cells/chains was also studied. The results showed that these compounds enhanced aggregation by both species. The addition of A. granulata EPS in Barra Bonita water, leaded to the formation of aggregates with larger relative surfaces (µm2) when compared to aggregates formed in Barra Bonita water in the absence of these compounds. This effect could be related to the hydrofobic characteristics of A. granulata EPS, which is composed of large amounts of terminal deoxy-sugars (fucose and rhamnose). When A. granulata chains were added to Barra Bonita water, the formed aggregates presented also larger relative surfaces. This increment leads to greater sinking rates and can promote important consequences for the cycling of matter in Barra Bonita reservoir.